Dynamics of composite nonlinear systems and materials for engineering applications and energy harvesting – The role of nonlinear dynamics and complexity in new developments - Litak, G.; Manoach, E. (The European physical journal. ST, Special topics, 2013)
This engineering research focus issue was inspired by the workshop organised by us on March 19th 2012 at the Lublin University of Technology (in the framework of CEMCAST) titled “Dynamics of functionally graded materials and systems with hysteresis” The collection of the present research papers followed our fruitful discussions focussing on “Dynamics of composite nonlinear systems and materials for engineering applications and energy harvesting” which is now the title of the present volume. In the next two sections we briefly discuss the topics included in this focus issue.